POLA-POLA KALIMAT DALAM PEMEROLEHAN BAHASA MELAYU TELUK BATANG KAYONG UTARA PADA ANAK USIA 3-4 TAHUN STUDI KASUS UNA RAISSA - Atika, Atika; Patriantoro, Patriantoro; Saman, Sesilya (Universitas Tanjungpura, 2023)
This study aims to describe sentence patterns in the acquisition of Malay language in Batang Kayong Utara Bay in children aged 3-4 years. Language acquisition In children aged 3-4 years is studied on the declarative, imperative, interrogative, and interjective sentence structure patterns obtained by Una Raissa. The method used in this study is the descriptive method. The form of research is qualitative. The source of the data is Una Raissa and the research data is all the utterances produced by Una Raissa in the form of sentence patterns in accordance with the formulation of the chosen problem. The data collection techniques used in this study are obesrvation techniques, proficient listening, recording techniques and recording techniques on data cards. The technique of testing the validity of the data is the persistence of observations and the adequacy of references. The results showed that: Declarative Sentence Patterns: (S-P) 88 patterns, (S-P-O) 7 patterns, (S-P-Pel) 15 patterns, (S-P-Ket) 5 patterns. Interrogative sentence patterns : (S-P) 27 patterns, (S-P-O) 2 patterns, (S-P-Pel) 3 patterns, (S-P-Ket) 3 patterns. Imperative sentence pattern : (S-P) 20 patterns, (S-P-O) 1 pattern, (S-P-Pel) 9 patterns, (S-P-Ket) 2 patterns. Interjective sentence patterns : (S-P) 19 patterns, (S-P-O) 1 pattern, (S-P-Pel) 3 patterns. From the results of data analysis, the most dominant sentence structure pattern obtained by children aged 3-4 years Una Raissa is the Subject-Predicate (S-P) pattern, which is 146 patterns, while the pattern that Una pronounces the least is Subject-Predicate-Caption (S-P-Ket), which is only 10 patterns. And the sentences that are most obtained by children aged 3-4 years Una Raissa are declarative sentences (news) which are 125 sentences, while sentences that Una rarely say are Interjective (exclamation) sentences, which are 25 sentences.